Persepsi dan Sikap Orang Tua tentang Pemberian Imunisasi Anak - Imelda Frastika; Sinta Nirwana Dwi Rahayu; Titusa Agustin; Lia Kartika (UIMA Press, 2020)
Abstract Introduction: Advances in biotechnology was giving benefits in the development of immunization-based substances. Immunization helps to reduce children morbidity. Children who missed basic immunization will have a high risk of experiencing serious illness. Preliminary data shows that 12 out of 30 parents are worried and doubtful about immunization and that optimal immunization coverage is not achieved. Objective: To find out the description of the perceptions and attitudes of parents and child immunization. Method: This research uses a quantitative descriptive method. Sampling technique using incidental sampling technique, amounting to 200 people. The standard instrument used to measure perception comes from Hemadiyan's (2017) questionnaire and attitude questionnaire from Yuliana (2010). The data analysis technique used is univariate analysis. Results: Most respondents had a good perception of immunization as many as 107 parents (53.5%), the majority of respondents had a good attitude towards giving immunizations, 113 people (56.5%), and full immunization of children as many as 156 respondents (78%). Conclusion: Nurses in hospital setting need to provide comprehensive education for parents about the benefits of providing child immunization. Nursing students together with paediatric nursing lecture can also produce immunization education materials in the form of audio visuals distributed to the community. This effort is expected to increase the coverage of basic immunization in Indonesia. Future studies can examine the relationship between parental perceptions and attitudes in immunization.